A call for a national paediatric cancer registry - Imam, Hibah Abid (Journal of the Pakistan Medical Association, 2026)
Dear Editor, Although paediatric cancers are far less prevalent,they are on the rise in Pakistan.Unfortunately, the lack of a national paediatric cancer registry restricts the ability to determine the incidence, trends, and outcome of cancers in this population. In Pakistan, the absence of a national paediatric cancer registry means that the exact number of childhood cancers remains unknown. As a result, most are diagnosed at advanced stages due to lack of awareness, proper training, and structured early detection protocols. Currently, we only have scattered data on childhood cancers, which is limited to hospital-based registries such as Shaukat Khanum Memorial Cancer Hospital, which is valuable but does not provide a comprehensive national epidemiological picture(1). Without proper centralised data, policymakers lack proper evidence needed to prioritise paediatric oncology in national health planning, and the allocation of resources remains challenging. This scattered reporting leads to underestimation, delayed diagnosis, irregular follow-up, and challenges in developing proper treatment guidelines (2). A registry would not only support research and guide the development of locally tailored treatment but also help in identifying disparities in access to care. Moreover, a national cancer registry would enable Pakistan to align with the WHO's Global Initiative for Childhood Cancer, which aims to increase the paediatric oncology survival rate up to 60% by 2030 (3). Presence of such registries is also important for long-term follow-up, and survivorship, planning geneticcounselling, and family risk screening services. A centralised paediatric cancer registry would enable accurate monitoring of incidence, early diagnosis, and treatment outcomes. Furthermore, it would aid in research, facilitate regional comparisons, and a direct national management plan could be made. (4). Finally, I would encourage Pakistan's health ministries, public health stakeholders, and paediatric oncology facilities to work together to create a national paediatric cancer registry. This is a very important step since it would be the foundation for equitable policies, evidence-based treatment, higher survival rates, and research investigations. This action will raise the nation's rates of children's cancer survival and care.